Bis(acetoxy)iodobenzene-Mediated Direct Transformation of α-Amino Acids into Nitriles - Li, Jing; Li, Shuangshuang; Gao, Mengyu (Synlett, 2025)
A novel bis(acetoxy)iodobenzene (PIDA)–mediated decarboxylative cyanation of α-amino acids to nitriles was developed using aqueous ammonia. Optimized conditions (CH₃CN/aqueous ammonia = 10/1, 2.5 equiv PIDA) afforded model compound 4-methylphenylacetonitrile in 87% yield. The method demonstrates broad substrate scope for both natural and unnatural amino acids bearing electronically diverse substituents (electron-donating and -withdrawing groups), yielding products in up to 92% yield with insensitivity to electronic effects. Gram-scale synthesis of 4-methylphenylacetonitrile (85% yield) confirmed the method’s scalability.
Keywords: Hypervalent iodine; Amino acids; Decarboxylation; Nitrile